Parental Alienation: The Blossoming of a Field of Study. (April 2019) - Harman, Jennifer J.; Bernet, William; Harman, Joseph
Parental alienation has been an unacknowledged and poorly understood form of family violence. Research on parental alienation and the behaviors that cause it has evolved out of decades of legal and clinical work documenting this phenomenon, leading to what could be considered a "greening, " or growth, of the field. Today, there is consensus among researchers as to what parental alienating behaviors are and how they affect children and the family system. We review the literature to detail what parental alienation is, how it is different from other parent–child problems such as estrangement and loyalty conflicts, and how it is perpetuated within and across different social systems. We conclude by highlighting research areas that need further investigation to develop and test effective solutions for ameliorating the devastating effects of parental alienation that, we posit, should be considered and understood not only as abusive to the child but also as a form of family violence directed toward both the child and the alienated parent.